PENGARUH INFORMASI AKUNTANSI TERHADAP KEBERHASILAN USAHA KECIL DAN MENENGAH STUDI PADA UKM PENGRAJIN KULIT DI BANTUL - Surya Kresna Anggara; Rohmad Yuliantoro Catur Wibowo (Universitas Ahmad Dahlan, 2015)
Accounting information useful for measuring and communicating information a finance company that desperately needs the management in the formulation of various decisions made to solve the problems faced by. This study attempts to get a clear on the influence of accounting information to successful smes craftsman the skin on bantul. The research is research quantitative with method the sample used is purposive sampling. The kind of data that used was the data primary. Data processing done using the tools spss 19 to technique regression analysis linear multiple. This research result indicates that information accounting simultaneously influential to successful smes. Variable financial report in partial do not affect. While planning effective, decision-making, the determination of hpp, and the determination of the selling price influential to successful smes. The result of this research also suggested that variable an independent in this study can influence the success of smes of 52 %, the rest influenced by a factor of other than this research.